1998
DOI: 10.1152/ajpheart.1998.275.5.h1759
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the ductus venosus in human fetuses: ultrasonographic evidence and mathematical modeling

Abstract: Autonomic regulation of blood flow through the fetal ductus venosus has been suggested, but the existence of a sphincter at the ductal entrance in human fetuses has yet to be established. In this paper two cases of apparent ductus venosus dilatation in two growth-restricted human fetuses are reported. Prolonged ultrasonographic analysis (45 min) showed rapid and substantial changes (>80%) of ductal diameters. Pulsed Doppler analysis was used to investigate flow velocity in the ductus venosus and umbilical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 18 publications
4
58
0
2
Order By: Relevance
“…While confirming the importance of extrinsic factors -resistance of the hepatic vascular district, magnitude of the umbilicocaval pressure gradient, blood viscosity -for the control of ductal flow (see Kiserud, 1999), this new line of investigation has yielded direct evidence, both in animals and humans, of an active tone regulation in the putative sphincter region as well as in the remainder of the vessel (Bellotti et al, 1998;Kiserud et al, 2000a). Coincidentally, it has demonstrated that ductus closure is delayed in preterm compared to term infants and, moreover, has ascertained that this sign of prematurity may subside after antenatal treatment with corticosteroids (Fugelseth et al, 1998;Loberant et al, 1999;Kondo et al, 2001).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…While confirming the importance of extrinsic factors -resistance of the hepatic vascular district, magnitude of the umbilicocaval pressure gradient, blood viscosity -for the control of ductal flow (see Kiserud, 1999), this new line of investigation has yielded direct evidence, both in animals and humans, of an active tone regulation in the putative sphincter region as well as in the remainder of the vessel (Bellotti et al, 1998;Kiserud et al, 2000a). Coincidentally, it has demonstrated that ductus closure is delayed in preterm compared to term infants and, moreover, has ascertained that this sign of prematurity may subside after antenatal treatment with corticosteroids (Fugelseth et al, 1998;Loberant et al, 1999;Kondo et al, 2001).…”
Section: Introductionmentioning
confidence: 80%
“…Recent advances in ultrasound imaging have shed light on this problem (Bellotti et al, 1998;2000;Kiserud, 1999;Kiserud et al, 2000b). While confirming the importance of extrinsic factors -resistance of the hepatic vascular district, magnitude of the umbilicocaval pressure gradient, blood viscosity -for the control of ductal flow (see Kiserud, 1999), this new line of investigation has yielded direct evidence, both in animals and humans, of an active tone regulation in the putative sphincter region as well as in the remainder of the vessel (Bellotti et al, 1998;Kiserud et al, 2000a).…”
Section: Introductionmentioning
confidence: 94%
“…We found visible pulsation in the umbilical vein at the abdominal inlet (umbilical ring) in 242/279 participants (87%, 95% CI 82-90), which was more common than in the cord (43/198, 22%, 95% CI [16][17][18][19][20][21][22][23][24][25][26][27] and in the intra-abdominal section of the vein (84/277, 30%, 95% CI 25-36) (P < 0.001) (Figure 2).…”
Section: Resultsmentioning
confidence: 97%
“…During abnormal cardiac physiology 25,26 an augmented atrial contraction is transmitted along the inferior vena cava and ductus venosus, which act as a transmission line to reach the intra-abdominal umbilical vein 9,15 . During hypoxia the ductus venosus distends 27,28 and reduces the reflections that normally take away most of the pulse energy before it reaches the umbilical vein 15 . A congestion in the umbilical vein (commonly seen in such situations 29 ) stretches the wall, or a twisting of the cord 30 causes a reduced compliance, which enhances the induction of velocity pulsation.…”
Section: Discussionmentioning
confidence: 99%
“…The vessel forms a preferential streaming of oxygenated blood to the foramen ovale and to the left heart and brain 6 . The ductus venosus appears to have a sphincter-like action that can regulate the amount of oxygenated blood shunted to the foramen ovale 10 .…”
Section: Discussionmentioning
confidence: 99%